2022
DOI: 10.21462/ijefl.v7i1.515
|View full text |Cite
|
Sign up to set email alerts
|

The Undergraduate Students’ Difficulties in Writing Thesis Proposal

Abstract: The purposes of this research were to find out the students’ difficulties in developing a paragraph and to understand the students’ difficulties in implementing the writing elements in writing their undergraduate thesis proposals. This research used the descriptive qualitative method. The instrument used in this research were interviews, documentation, and Oshima & Hogue’s Paragraph Rubric. The research subject was 7 eighth-semester students of UINSI Samarinda. The data were collected from the background o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Therefore, undergraduate students studying English as a foreign language (EFL) often encounter significant challenges in writing their theses (Lestari., 2020). In the research conducted by, (Fauzan, Hasanah, & Hadijah,.2022;Aldabbus & Almansouri,.2022;Fitria, TN, 2022) found that students have difficulty in developing paragraphs and writing topic sentences due to limited vocabulary, lack of ideas, confusion at the beginning of the paragraph, students' lack of ability to understand the systematics of writing a thesis, tend to use translation tools, difficulties in grammar and punctuation the right way to write a thesis correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, undergraduate students studying English as a foreign language (EFL) often encounter significant challenges in writing their theses (Lestari., 2020). In the research conducted by, (Fauzan, Hasanah, & Hadijah,.2022;Aldabbus & Almansouri,.2022;Fitria, TN, 2022) found that students have difficulty in developing paragraphs and writing topic sentences due to limited vocabulary, lack of ideas, confusion at the beginning of the paragraph, students' lack of ability to understand the systematics of writing a thesis, tend to use translation tools, difficulties in grammar and punctuation the right way to write a thesis correctly.…”
Section: Introductionmentioning
confidence: 99%